2016
DOI: 10.17140/hroj-2-126
|View full text |Cite
|
Sign up to set email alerts
|

Small Ventricular Septal Defect Considered Not Requiring Surgical Closure: The Frequency of Developing Complications in Our Center

Abstract: Objectives:The study was conducted to check the frequency of development of complication in the patients with small Ventricular Septal Defects (VSDs) considered not requiring surgical closure during childhood. Methods: A descriptive study was conducted on children from January 2015 to December 2015 at Children Hospital and Institute of Child Health, Lahore, Pakistan. The data with isolated VSDs considered too small to require surgery from 1 month to 15 years of age were reviewed. The data was analyzed with SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…According to AHA guidelines and NICE guidelines VSD is considered as moderate to low risk for developing infective endocarditis, as per that only good dental hygiene and skin care rather antibiotic prophylaxis is sufficient to prevent IE. On the other hand, a study conducted in Lahore, Pakistan reported significant risk of IE with small VSD and recommended use of prophylactic antibiotics in patients with even small VSD 6 .…”
Section: Introductionmentioning
confidence: 99%
“…According to AHA guidelines and NICE guidelines VSD is considered as moderate to low risk for developing infective endocarditis, as per that only good dental hygiene and skin care rather antibiotic prophylaxis is sufficient to prevent IE. On the other hand, a study conducted in Lahore, Pakistan reported significant risk of IE with small VSD and recommended use of prophylactic antibiotics in patients with even small VSD 6 .…”
Section: Introductionmentioning
confidence: 99%